2015
DOI: 10.1161/strokeaha.114.006476
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke and Intracranial Hemorrhage With Aspirin, Dabigatran, and Warfarin

Abstract: In Chinese patients with atrial fibrillation, the benefits of warfarin therapy for stroke prevention and ICH risk are closely dependent on the quality of anticoagulation, as reflected by TTR. Even at the top TTR quartile, warfarin was associated with a higher stroke and ICH risk than dabigatran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
78
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 39 publications
5
78
2
Order By: Relevance
“…The J‐ROCKET AF trial (Japanese Rivaroxaban Once Daily Oral Direct Factor Xa Inhibition Compared With Vitamin K Antagonism for Prevention of Stroke and Embolism Trial in Atrial Fibrillation) showed that the pharmacokinetic profiles of a 15‐mg dose of rivaroxaban in Japanese patients was similar to the 20‐mg dose in white patients, indicating that low‐dose rivaroxaban with 15/10 mg is adequate for stroke prevention in AF patients 35. Chan et al also reported that low‐dose dabigatran was associated with the lowest risk of ischemic stroke and ICH compared with warfarin with a variety of quality controls in elderly Chinese with AF 36, 37, 38. Further studies are warranted to determine the so‐called “optimal” dose of NOACs in Asians with AF.…”
Section: Discussionmentioning
confidence: 85%
“…The J‐ROCKET AF trial (Japanese Rivaroxaban Once Daily Oral Direct Factor Xa Inhibition Compared With Vitamin K Antagonism for Prevention of Stroke and Embolism Trial in Atrial Fibrillation) showed that the pharmacokinetic profiles of a 15‐mg dose of rivaroxaban in Japanese patients was similar to the 20‐mg dose in white patients, indicating that low‐dose rivaroxaban with 15/10 mg is adequate for stroke prevention in AF patients 35. Chan et al also reported that low‐dose dabigatran was associated with the lowest risk of ischemic stroke and ICH compared with warfarin with a variety of quality controls in elderly Chinese with AF 36, 37, 38. Further studies are warranted to determine the so‐called “optimal” dose of NOACs in Asians with AF.…”
Section: Discussionmentioning
confidence: 85%
“…It is estimated that 10-30% of AF are not diagnosed 32,35 and more than 40% of patients at high risk of stroke fail to receive guideline-recommended oral anticoagulant treatment 11,35 . 39 and increased risk of stroke 40,41 . All these gaps highlight unmet needs for stroke prevention in undiagnosed and undertreated AF, which will shed light on the strategies needed to eliminate disparities in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…8 What are the implications of these findings for clinical practice? The results by Ho et al 5 add to the accumulating and now compelling evidence that anticoagulation offers important benefits to East Asian patients with atrial fibrillation. Healthcare providers and patients in Asian countries must take note, and urgently implement readily available and highly effective treatments to reduce the enormous burden of preventable stroke.…”
mentioning
confidence: 87%
“…The data presented by Ho et al 5 alert clinicians and patients to the requirement to evaluate better methods of healthcare delivery, so that highly effective, evidence-based therapies are appropriately implemented. At the same time, there also remains a need for further studies to understand the risk factors better, causes, and consequences of bleeding in patients with atrial fibrillation who are treated with antithrombotic therapy because fear of bleeding remains an important barrier to the appropriate use of anticoagulant therapy in this population.…”
Section: Intensity and Quality Of Warfarin Anticoagulation In Chinesementioning
confidence: 99%
See 1 more Smart Citation